CD44v9 is associated with epithelial‐mesenchymal transition and poor outcomes in esophageal squamous cell carcinoma. (26th November 2018) - Taniguchi, Daisuke; Saeki, Hiroshi; Nakashima, Yuichiro; Kudou, Kensuke; Nakanishi, Ryota; Kubo, Nobuhide; Ando, Koji; Oki, Eiji; Oda, Yoshinao; Maehara, Yoshihiko
Abstract: CD44 serves as a marker of cancer stem cells. Alternative splicing generates the CD44v9 isoform. Cancer stem cells are associated with the epithelial‐mesenchymal transition in cancers, although little is known about their role in esophageal squamous cell carcinoma. Here, we aimed to clarify the relationship between CD44v9 expression, the epithelial‐mesenchymal transition, and clinicopathological features of patients with esophageal squamous cell carcinoma. CD44v9 levels were higher at the tumor invasive front compared with the center of the tumor and higher in metastatic lymph nodes compared with primary tumors. High levels of CD44v9 at the tumor invasive front were significantly associated with deeper tumor invasion and shorter overall survival and recurrence‐free survival. The expression of CD44v9 was increased by treatment with transforming growth factor‐β, which induced esophageal squamous cell carcinoma cells to undergo the epithelial‐mesenchymal transition. Moreover, inhibition of CD44v9 expression decreased the migration and invasiveness of esophageal squamous cell carcinoma cells. These results indicate that the expression of CD44v9 at the tumor invasive front induced by stemness was strongly associated with the epithelial‐mesenchymal transition and poor prognosis of patients with esophageal squamous cell carcinoma. CD44v9 may therefore serve as a novel prognostic biomarker and a potential therapeutic target for esophageal squamous cell carcinoma. Abstract : CD44v9 expression at the tumor invasive front is associated with the EMT, tumor invasion. Moreover, CD44v9 expression at the TIF was an independent prognostic factor of overall survival and recurrence‐free survival. We conclude that CD44v9 represents a novel prognostic biomarker and a potential therapeutic target for ESCC.